Laccase-catalyzed green synthesis and cytotoxic activity of novel pyrimidobenzothiazoles and catechol thioethers12. Issue 28 (20th March 2017) - Abdel-Mohsen, H. T.; Conrad, J.; Harms, K.; Nohr, D.; Beifuss, U.
Abstract : Laccase-catalyzed green reaction between catechols and 2-thioxopyrimidin-4-ones delivers novel pyrimidobenzothiazoles and catechol thioethers with antiproliferative activities against HepG2 cell line. Abstract : The laccase-catalyzed reaction between unsubstituted catechol and 2-thioxopyrimidin-4(1 H )-ones using aerial O2 as the oxidant delivers novel pyrimidobenzothiazoles with high yields in an aqueous solvent system under mild reaction conditions. With 4-substituted catechols, catechol thioethers are formed exclusively. The synthetic protocols developed provide a sustainable approach for these compound classes. In addition, the cytotoxicity of the products against HepG2 cell line is reported. Most compounds exhibit antiproliferative activities with IC50 values at the micromolar level. A structure–activity relationship study will facilitate the further development of these compounds as cytotoxic agents.